2004
DOI: 10.1038/sj.bjc.6601860
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinoma after Chernobyl latent period, morphology and aggressiveness

Abstract: The large numbers of papillary thyroid carcinomas that have occurred in those exposed to high levels of short-lived isotopes in fallout after Chernobyl provide a unique opportunity to correlate latency and tumour biology. We show that short latency is associated with tumours with a phenotype that is significantly less structurally differentiated, shows significantly less peritumour fibrosis, and significantly more invasive spread when compared to tumours with a longer latent period. In contrast, the type of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
3
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 17 publications
4
109
3
2
Order By: Relevance
“…These findings on post-Chernobyl PTCs developed with short and long latency after irradiation suggest that multiple clones develop from follicular cells to form papillary cancer. This interpretation is supported by other studies on papillary cancers (Sugg et al, 1998;Tallini et al, 1998;Fusco et al, 2002) and the recent demonstration that the histology of post-Chernobyl PTCs is inhomogeneous and is changing with time after the accident (Williams et al, 2004). This is borne out in this study, as the proportion of tumours of a solidfollicular morphology is increased in those of longer latency, and those of a purely solid morphology is decreased (Figure 3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings on post-Chernobyl PTCs developed with short and long latency after irradiation suggest that multiple clones develop from follicular cells to form papillary cancer. This interpretation is supported by other studies on papillary cancers (Sugg et al, 1998;Tallini et al, 1998;Fusco et al, 2002) and the recent demonstration that the histology of post-Chernobyl PTCs is inhomogeneous and is changing with time after the accident (Williams et al, 2004). This is borne out in this study, as the proportion of tumours of a solidfollicular morphology is increased in those of longer latency, and those of a purely solid morphology is decreased (Figure 3).…”
Section: Discussionsupporting
confidence: 90%
“…These papillary carcinomas were then further subdivided according to their dominant architectureeither papillary, follicular or solid. This categorisation has been used in other papers detailing the morphological subtypes of papillary carcinoma post-Chernobyl (Williams et al, 2004). Where two components were present in equal proportions, both features are given (e.g.…”
Section: Patient Samplesmentioning
confidence: 99%
“…(5)] in the incidence of childhood thyroid carcinoma has been observed in Belarus and Ukraine and to a lesser extent in the Russian Federation starting in 1990 (6). A comparison of these tumors with carcinomas in patients in the same age group in Italy and France revealed that the post-Chernobyl thyroid carcinomas were less influenced by gender and were nearly always papillary (7). A solid papillary histological type was found in 93% of children in the Ukraine (8), and an increased prevalence of ultrasonographic thyroid abnormalities (nodules, cysts) was found (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the "marked solid component and more aggressive behavior [which] characterize tumors with shorter latency" (22) were, obviously, the features of older and more advanced cancers. Then it becomes clear why "short latency is associated with tumors with a phenotype that is significantly less structurally differentiated, shows significantly less peritumor fibrosis, and significantly more invasive spread when compared to tumors with a longer latent period" (36). The concluding point is that information on molecular-genetic and immunological characteristics of supposedly radiogenic post-Chernobyl tumors, accumulated as a result of international research, requires re-evaluation and new interpretation.…”
Section: öZmentioning
confidence: 99%